Kānsadet phrarātchadamn̄œn ȳưan Saharat ̌Ameērikā læ prathēt Kh̄œnādā pen thāng rātchakān rawāng wantȟi 1-29 Mithunāyon Phutthasakkarāt 2510 (Samnak Rātchalēkhāthikān, 1994)
Record of visit of Their Majesties the King Bhumibhol of Thailand to American and Canada, 1967.